PENGARUH PENGGUNAAN STRATEGI PEMBELAJARAN ACTIVE KNOWLEDGE SHARING TERHADAP HASIL BELAJAR BIOLOGI DITINJAU DARI GAYA BELAJAR SISWA KELAS X SMA NEGERI 5 SURAKARTA TAHUN PELAJARAN 2011/2012 - Purwaningsih, Desi; Harlita, Harlita; Sugiharto, Bowo (P Biologi FKIP UNS Surakarta, 2011)
ABSTRACT - This research aims to find out : (1) the effect of the implementation of active learning strategy; Active Knowledge Sharing strategy towar student achievement in Biology at the grade of Class X at SMA Negeri 5 Surakarta; (2) the effect of students?learning style toward student achievement in Biology at the grade of Class X at SMA Negeri 5 Surakarta; and (3) the interaction between learning strategy and learning style simultaneously toward student achievement in Biology at the grade of Class X at SMA Negeri 5 Surakarta. Learning process at school which is dominated by teacher causes student haven't got active role. The different learning styles of the students necessitate the teacher has to use varied and innovative learning strategyes that enable students to be actively involved in learning process. The use of those strategies are expected to be able of optimizing students achievement. This research belongs to Quasi experiment which use Randomized Control Only Design. The independent variables of this research are learning strategy and learning style, while the students? achievement in Biology is the dependent variable. The population of this research is all student of Class X at SMA Negeri 5 Surakarta in Academic Year 2011/2012. The sample of this research are the students of class X-5 as the control group and the students of class X-4 as the experimental group that are taken by cluster random sampling. The data of the students? achievement are completed by test and observation techniques. Learning style is meansured by questionnaires. The analysis technique of this research is two away anava in different cell while the advance analysis is Bunfferoni test. From the results, it can be concluded that: : 1) Active Learning; Active Knowledge Sharing strategy has significant effect toward biology?s student achievement (cognitive, affective, and psycomotor) of Class X at SMA Negeri 5 Surakarta; 2) Learning style does not have significant effect toward biology?s student achievement (cognitive, affective, and psycomotor) of Class X at SMA Negeri 5 Surakarta; 3) There is an interaction between learning strategy and learning style toward biology?s student achievement (cognitive, affective, and psycomotor) of Class X at SMA Negeri 5 Surakarta. Key Word: Student Achievement In Biology, Active Learning, Active Knowledge Sharing, Learning Style